Natural Environment and its Influence on the Psyche of the Ukrainian Ethnos - Snizhko, Valeriy (Skhid : analitychno-informat͡s︡iĭnyĭ z͡h︡urnal, 2025)
The article is devoted to determining the role of the natural environment in shaping the mental foundations of the Ukrainian ethnos. It is argued that a specific locality in Europe determines the psycho-ethnic basis of Ukrainian society, which undergoes a multi-vector genesis precisely in the special natural conditions of ‘the integrity of space and time.’ The geopsychological influence of the biogeographical and specific biocenotic environment on the somatopsychic state of the human mind and the regional features of such influence, which are manifested in specific ethnic psychotypology, have been determined. These psychotypological characteristics are embodied in the way of thinking of representatives of certain communities, which today is referred to as “mentality”. We approach these states of the human psyche after coming from the archetypal foundations or prototypes of the human mentality. Therefore, we move on from various archetypal foundations that significantly influence the peculiarities of behaviour and economic activity (in particular, archetypes “man-plant” and “man-animal”) to the consideration of societies dominated by the so-called “agricultural consciousness”. Such societies always progress because, after having ensured their hunger-free living, they always strive to creatively improve their well-being, namely comfort, and actively resort to art in the form of the creation of a specific product. In return, people with the collecting consciousness and their own original “art”, evolve into the selective or appropriating consciousness, when the creative approach leads to the encroachment not only on the Nature, but also on those societies that generate the product the selectors steal. The agricultural reasoning instead offers agrotechnologies, pottery, cattle breeding, cooperage, agricultural inventory and many other things such as art, writing, literature, etc.